A systematic review of motivated system justification among youth - Biedron, Henry Winslow; Reimer, Nils Karl; Balcetis, Emily (Frontiers in Social Psychology, 2024)
IntroductionRedressing social inequities requires people to fight for social change and upend the status quo. However, beliefs that the current state of affairs operates in a just and fair way, referred to as system justifying tendencies, stand as obstacles to social change. With this investigation, we asked if there is evidence to suggest that youth hold system justifying beliefs.MethodsUsing PRISMA guidelines for a systematic review, we identified studies that measured system justifying beliefs among children [ages 6-12] and adolescents [ages 13-18].ResultsThis review synthesizes evidence that, first, both cohorts of youth hold beliefs that the status quo operates in a just and fair manner and that, second, system justification theory and its predictions extend to youth demographics. We note antecedents to system justifying tendencies in youth including demographic and situational factors. Moreover, we find evidence of the palliative consequences of system justifying tendencies in youth.DiscussionWe offer recommendations for future research into system justification among youth demographics.